2012
DOI: 10.1002/ijc.27823
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumoral activity of oncolytic herpes simplex virus with gemcitabine using colorectal tumor models

Abstract: To enhance the oncolytic activity of herpes simplex viruses (HSVs) control of immune-suppression and immune-resistance by cancer cells is important. Myeloid-derived suppressor cells (MDSCs), which interfere with tumor-suppressive environments, are inhibited by gemcitabine (GEM) treatment. We investigated the oncolytic activity and systemic antitumor immunity induced by oncolytic HSVs in combination with GEM treatment. A mouse model with subcutaneous tumors on both sides of the lateral flanks was used. A highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…As shown in Fig. 6A and B, plaques formed by KGN bearing wild-type gD were readily detected and similar in size, irrespective of cellular EGFR expression, in accordance with the reported HSV susceptibility of CT26 cells (59,60). In contrast, KGNE-BhKt developed syncytia on CT26-EGFR acceptor cells, while only single infected (presumably donor) cells or very small foci of single infected cells were detected in mock-transduced CT26 acceptor cells (Fig.…”
Section: Introduction Of Syncytial Mutations Into An Egfr-retargeted supporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 6A and B, plaques formed by KGN bearing wild-type gD were readily detected and similar in size, irrespective of cellular EGFR expression, in accordance with the reported HSV susceptibility of CT26 cells (59,60). In contrast, KGNE-BhKt developed syncytia on CT26-EGFR acceptor cells, while only single infected (presumably donor) cells or very small foci of single infected cells were detected in mock-transduced CT26 acceptor cells (Fig.…”
Section: Introduction Of Syncytial Mutations Into An Egfr-retargeted supporting
confidence: 86%
“…CT26 cells are susceptible to wild-type HSV and have been used by others to test the efficacy of oncolytic HSVs (59,60). CT26-EGFR cells were infected with KGN or KGNE-BhKt at an MOI of 10 to achieve 100% infection.…”
Section: Introduction Of Syncytial Mutations Into An Egfr-retargeted mentioning
confidence: 99%
“…The therapeutic benefits of using these OV-drug combinations depend on several factors, including the type of OV-drug combination used, the timing, frequency, and dosage of drug administration, and the cancer type targeted. However, given that these immunomodulatory drugs have other antitumoral effects, few studies have directly assessed their ability to deplete MDSCs in each context (135, 136). Notably, use of these drugs to deplete MDSCs can also positively or negatively affect oncolytic virotherapy.…”
Section: Combining Immunomodulatory Chemotherapy With Oncolytic Virotmentioning
confidence: 99%
“…Myeloid suppressor cells are attractive targets for therapeutic investigations (85). Related to oncolytic virotherapy, it was shown that the combination with gemcitabine, which is a chemotherapeutic agent depleting MDSC populations, increases antitumoral immune responses (86, 87). …”
Section: Myeloid Cellsmentioning
confidence: 99%